PENGARUH KUNJUNGAN WISATAWAN DAN PENERIMAAN SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KLUNGKUNG - Ni Ketut Rendi Astuti; Ni Made Gunastri (Forum Manajemen STIMI Handayani Denpasar, 2013)
This research is carried out based on the little contribution income oftourism sector towards the real income of Klungkung regency for eight years whereas the tourism facilities that have been availabel sufficiently to attract the moretotal tourists visit. The variable use in this researdh involves : the total tourist visit (X1), the totaltaxes of restaurants and hotels (X2), the total retribution of tourism object (X3) andtotal real income (Y) of Klungkung Regency in the year 2003 to 2010. The instrument analysis which is used in this research are regression linier is use to analyze the influence of the total tourist visit, total taxes in restaurant and hotel income, tourist objects retribution toward the real income of Klungkung regency foreight years 2003 to 2010 The result of the research is that the total tourist visit, restourant and hotels incometaxes, and retribution of tourist resorts places all together significantly affectedthe original Regional Revenues of Klungkung Regency from 2003 to 2010. Thetotal tourist visit place partially and significantly affected the Original RegionalRevenues of Klungkung from 2003 to 2010, The taxes imposed upon the hotel andrestourant partially but insignificantly affected the Original Regional Revenues ofKlungkung from 2003 to 2010. And retribution of tourist risorts places partiallybut insignificantly but insignificantly affected the Original Regional Revenues from2003 to 2007.